2014
DOI: 10.1177/039463201402700410
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of HMGB1 Expression in Human Gastric Cancer

Abstract: High mobility group box 1 (HMGB1) has been proved to be implicated in a variety of cell physiological and pathological behaviors including immune response, inflammation and cancer. Accumulating evidence suggests that HMGB1 plays a critical role in the development and progression of multiple malignancies. However, the clinical significance and prognosis of HMGB1 expression in some cancers remain controversial. The present study aimed to investigate whether overexpression of HMGB1 is an independent prognostic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…Additionally, HMGB proteins are subdivided into HMGB1, HMGB2, and HMGB3, all of which contain two HMG-box domains and a highly acidic Cterminal tail [10,11]. The current study found the expression levels of HMGB1 gene were significantly higher than that of the corresponding normal tissues in a variety of tumor tissues, including colorectal cancer, breast cancer, pancreatic cancer, melanoma, et al, which suggested that HMGB1 was involved in the occurrence and development of tumors [12][13][14][15][16]. Dong found that knockdown of the HMGB1 expression inhibited tumor growth and metastasis in human liver cancer through AKT-mediated regulation of Ki-67 and MMP-2 expression [17].…”
Section: Introductionsupporting
confidence: 48%
“…Additionally, HMGB proteins are subdivided into HMGB1, HMGB2, and HMGB3, all of which contain two HMG-box domains and a highly acidic Cterminal tail [10,11]. The current study found the expression levels of HMGB1 gene were significantly higher than that of the corresponding normal tissues in a variety of tumor tissues, including colorectal cancer, breast cancer, pancreatic cancer, melanoma, et al, which suggested that HMGB1 was involved in the occurrence and development of tumors [12][13][14][15][16]. Dong found that knockdown of the HMGB1 expression inhibited tumor growth and metastasis in human liver cancer through AKT-mediated regulation of Ki-67 and MMP-2 expression [17].…”
Section: Introductionsupporting
confidence: 48%
“…HMGB1, a highly conserved DNA-binding protein, was found to be a direct and functional downstream target of miR-665 in RB. HMGB1 is located on chromosome 8q22 and has been found to be upregulated in various human malignancies, including endometrial carcinoma, 38 gastric cancer, 39 hepatocellular carcinoma, 40 and renal cell carcinoma. 41 It is also highly expressed in RB, and its overexpression is closely associated with poor tumor differentiation and optic nerve invasion.…”
Section: Discussionmentioning
confidence: 99%
“…18 studies met our inclusion criteria and were finally included for the analysis, involving 11 different tumor types (3 studies of gastric cancer [14–16], 4 of colorectal cancer [17–20], 2 of hepatocellular carcinoma [21, 22], 2 of pancreatic cancer [23, 24], 1 of nasopharyngeal carcinoma [25], 1 of head and neck squamous-cell carcinoma [26], 1 of esophageal cancer [27], 1 of malignant pleural mesothelioma [28], 1 of bladder cancer [29], 1 of prostate cancer [30], and 1 of cervical carcinoma [31]) (Figure 1). A total of 2249 participants were analyzed for the association between HMGB1 expression and disease prognosis, of which 2090 (92.9%) and 1247 (55.4%) ones were respectively included into overall survival (OS) and progression-free survival (PFS) analyses.…”
Section: Resultsmentioning
confidence: 99%